The Role Of Religion in Dealing With Natural Disaster Trauma: A Case Study Of The Survivor Of Aceh’s Earthquake And Tsunami in 2004 - Pratama, Dito Alif (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
Natural disasters can cause deep trauma to survivors, affecting various aspects of their lives, such as their mental health and quality of life. This study aimed to explore the role of religion in helping victims of natural disasters overcome the trauma caused by the 2004 earthquake and Tsunami in Aceh. The research method used a qualitative approach by interviewing several victims who survived the disaster. The data obtained from the interviews were then analyzed using a thematic analysis approach, and the results showed that religion played a significant role in helping victims overcome disaster trauma. In the face of losing family members, homes, and other assets, their religious beliefs provide emotional support and strength to carry on with life. Prayers, religious rituals, and participation in faith-based community activities helped them feel connected to fellow victims and alleviated their feelings of loneliness. Religion also served as a source of comfort for victims. Belief in greater divine power helps victims go through the recovery process with more confidence. Acceptance of fate and belief in justice helped them overcome feelings of confusion and anger towards their situation. However, the research also identified some challenges in integrating religious aspects into post-disaster recovery efforts. Differences in religious beliefs and individual interpretations of disaster events can cause tension and conflict within communities. Therefore, an approach that is inclusive and respectful of the diverse religious beliefs is necessary to support a holistic recovery process. This study concludes that religion plays an important role in helping victims of natural disasters cope with trauma and recover. Implementing a religiously sensitive approach to post-disaster relief efforts can increase the effectiveness and sustainability of the recovery efforts. The results of this study are expected to provide insights for humanitarian aid practitioners, researchers, and other relevant parties to develop more effective and sustainable interventions for victims of natural disasters in the future.